Analysis of RT-qPCR Data - Perkins, James R.; Rahman, Nor Izayu Abdul; Kohl, Matthias (International Journal of Statistics in Medical Research, 2012)
We give a brief overview of the necessary steps in the analysis of real-time reverse transcription quantitative polymerase chain reaction (RT-qPCR) data. We cover determination of amplification efficiency, background correction, normalization, quality control, and statistical analysis.